(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2009)
This paper is an appreciation and a critical examination of Spinelli’s book Practising Existential Psychotherapy: The Relational World. It uses the points raised by the author to question the validity of the current emphasis therapy culture places on relatedness – and its subsequent avoidance of existential aloneness – and proposes that ’relatedness’ is Platonic nostalgia of unity as well as a pragmatist misreading of the wider notions – derived from Zen philosophy and from Nietzsche - of interdependence and groundlessness. It also discusses the other two tenets proposed by Spinelli, i.e. anxiety and uncertainty and the way these reflect on the problem of nihilism, evaded by the current therapy zeitgeist.